A novel approach to a rabies vaccine based on a recombinant single-cycle flavivirus vector. Issue 49 (14th December 2017) - Giel-Moloney, Maryann; Rumyantsev, Alexander A.; David, Fred; Figueiredo, Monica; Feilmeier, Brad; Mebatsion, Teshome; Parrington, Mark; Kleanthous, Harry; Pugachev, Konstantin V.
Highlights: Viral vectors can provide advantages in the development of novel vaccines. The RepliVax® platform was successfully targeted to the rabies virus G protein. The single-cycle vaccine candidate is highly immunogenic and efficacious. The vaccine candidate elicited highly durable, two-year long, immunity in dogs. Abstract: The RepliVax® vaccine (RV) platform is based on flavivirus genomes that are rationally attenuated by deletion. These single-cycle RV vaccine candidates targeting flavivirus pathogens have been demonstrated to be safe, highly immunogenic, and efficacious in animal models, including non-human primates. Here we show utility of the technology for delivery of a non-flavivirus immunogen by engineering several West Nile-based RV vectors to express full-length rabies virus G protein. The rabies virus G protein gene was incorporated in place of different West Nile structural protein gene deletions. The resulting RV-RabG constructs were demonstrated to replicate to high titers (8 log10 infectious particles/ml) in complementing helper cells. Following infection of normal cells, they provided efficient rabies virus G protein expression, but did not spread to surrounding cells. Expression of rabies virus G protein was stable and maintained through multiple rounds of in vitro passaging. A sensitive neurovirulence test in 2–3 day old neonatal mice demonstrated that RV-RabG candidates were completely avirulent indicative of high safety. We evaluated the RV-RabG variants in several animal models (mice, dogs, and pigs) and demonstrated that a single dose elicited high titers of rabies virus-neutralizing antibodies and protected animals from live rabies virus challenge (mice and dogs). Importantly, dogs were protected at both one and two years post-immunization, demonstrating durable protective immunity. The data demonstrates the potential of the RepliVax® technology as a potent vector delivery platform for developing vaccine candidates against non-flavivirus targets.